Pelatihan Penyusunan Rubrik Penilaian Hasil Belajar di Pondok Pesantren Darul Ukhuwah Malang: Community Service Program on Developing Learning Assessment Rubrics at Darul Ukhuwah Islamic Boarding School, Malang - Ihwan Mahmudi; Siti Nikmatul Rochma (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
This community service program aimed to enhance teachers' competence at Pondok Pesantren Darul Ukhuwah Malang in designing and implementing performance assessment rubrics to promote objective, standardized evaluations. The training was initiated due to the absence of established rubrics for assessing students’ practical skills, such as religious practices, speeches, and oral examinations, which had previously been conducted subjectively and inconsistently among teachers. The program was carried out through three stages: planning, implementation, and evaluation. The training activities included discussions, conceptual presentations, and group-based hands-on rubric development. The results showed a significant improvement in teachers’ ability to develop performance rubrics, as demonstrated by the successful creation of rubrics for ablution practice, Arabic speech, Arabic oral examinations, and Qur’an recitation. However, the reflection session revealed some areas for improvement, particularly the fact that several assessment indicators had not yet been derived from a comprehensive literature review. Overall, the training effectively strengthened teachers’ understanding and skills in rubric development. Nevertheless, continuous mentoring and follow-up training are recommended to refine rubric design and ensure sustainable enhancement of assessment quality within the pesantren environment.